LA RISPECIFICAZIONE DEL TRASMETTITORE E DEL RECETTORE Ãˆ UNA NUOVA FORMA DI PLASTICITÃ€ DEL SISTEMA NERVOSO NELLâ€™ADULTO (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
After some words on the scientific role of Professor Paolo Mantegazza atthe University of Milan (4, 5, 6), I briefly illustrate some studies related to the occurrence of neurotransmitter and receptor re-specification in the adult animals. The greatdiscoveries of the early twentieth century on neuronal communication have established that the majority of communication between nerve cells occurs through a special structure, the synapse, allowing the one-way transfer of information between twocells through the release of a neurotransmitter from the presynaptic cell and its recognition by receptors localized in the postsynaptic cell. According to H. Dale axiom (9) each neuron could be identified on the basis of the neurotransmitter released and theinnervated cell by the type of receptors expressed; then neurons could be classified asexcitatory if they release acetylcholine, glutamate or other transmitters, or inhibitory ifthey release GABA or glycine. However, in recent years many studies have shown that, especially during development, a neuron could release and co-release several neuro-transmitters, sometimes even simultaneously, changing its classification from excitatory to inhibitory and vice versa(7). This researches opened a new field of study onsynaptic plasticity: the neurotransmitter and receptor re-specification. Our group, together with Prof. Mantegazza, tried to â€œforceâ€ it through experiments of denervation and heterologous re-innervation in the autonomic nervous system and at the neuromuscular junction. In a first series of experiments we studied the regenerative capabilities of the peripheral nervous system in three experimental models: a) re-innervation of the denervated superior cervical ganglion (SCG) (14, 15, 22) by cholinergicefferent vagal fibers, b) re-innervation of peripheral effectors smooth muscles (nicti-tating membrane) by the cholinergic preganglionic fibers; c) re-innervation in an in vivo transplant model of peripheral organs by the SCG. In these researches we haveestablished: 1) that a sympathetic ganglion could be re-innervated by vagal fibersforming normal ganglionic synapses, but with a strong reshaping, in vivo, of the cen-tral neural circuits so that sympathetic stimuli occurred through a vagal excitation; 2) preganglionic cholinergic fibers innervate the smooth muscle of the nictitating mem-brane releasing catecholamines instead of acetylcholine; 3) that in an in vivo model ofSCG transplant together with iris or adrenal medulla fragments, the SCG was able todistinguish between organs that required a postsynaptic innervation, iris, which wasinnervated, and organs that require a presynaptic innervation, the adrenal medulla,that was not innervated. We were then in the presence, even in the adult animal, of anew nervous plasticity with re-specification the neurotransmitter. These resultsdemonstrate that heterologous innervation could â€œforceâ€ plasticity in adult peripheralnervous system, alters the biological properties of neurons, upsets central neuronal circuits, but continues to maintain in experimental transplants basic rules of innervation between neurons and peripheral organs. Thirty years later, the group of prof. Brunelliin Brescia (23), along with pharmacologists and physiologists, had highlighted the pos-sibility of re-innervate striated muscles in a functional way with nerve fibers derivedfrom the red nucleus of the vestibular complex. The interest was, once again, in thefact that the re-innervating fibers were of glutamatergic type, and not cholinergic likethose of normal motor neurons, and that neuromuscular transmission was transformedfrom nicotinic cholinergic in glutamatergic. A new type of plasticity: the receptor re-specification had occurred also in this experimenal model. In close cooperationbetween our Milan and the Brescia group we could reconfirm with more appropriateexperiments that the re-innervation occurred; that neuromuscular junction had a glutamatergic transmission; that new re-innervating fibers made synapses at the same sitesof the previous neuromuscular junctions; that the new fibers release glutamate; andthat muscle cells expressed new glutamate receptors (24). Once again we were in thepresence of an extraordinary phenomenon of synaptic plasticity, in this case a receptorre-specification, and again with a strong impact on the central nervous system circuits.These experiences, along with many others now available in the literature, show thatthe adult peripheral nervous system, both autonomous and musculoskeletal, has aplasticity unthinkable before and open a field of great interest aiming at the understanding how neuronal specificity is regulated and at the investigation of non-canonical, but perhaps functional, re-innervation experiments in transplants and in post-traumatic surgery.